Production and Quality Semen From Candidate Bull Zuriat With Progeny Test at BIB Lembang - Elma Rohlyharni; Afton Atabany; Bagus Priyo Purwanto (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
The study aimed to evaluate the quality and production of semen for candidate bull (Folegan, Aris, Flate, Flanggo). The research was carried out from March to May 2022 at BIB Lembang, West Java. The materials used were secondary data recordings of semen quality and production from 4 candidate bulls as Zuriat tests in 2016 - 2020. Data were analyzed descriptively. The results of the study from four candidate bulls were the concentration of spermatozoa: 1209,35±269,92, 1181,47±238,92, 1137,22± 207,73 and 115,25±261,36 (106 /mL); mass motion: 2,01±0,09, 2,01±0,07, 2,00±0,05 and 2,00±0.05; individual motility: 71,01±0,02, 70,89±0,02, 70,82±0,19 and 70,70±0,02(%); pH: 6,60±0,16, 6,58±0,16, 6,58±0,15 and 6,56±0,15; semen volume: 6,76±2,03, 6,59±2,15, 6,42±1.49 and 5,47±1,52 (mL), and frozen semen production: 295,40±96,92, 293,40±91,40, 265,90±90,81 and 227,66±66,01. The study concludes that the quality and production of semen of the four candidate bulls is normal and suitable to be used as proven bulls.